2014
DOI: 10.1371/journal.pone.0114748
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Significance of DC-SIGN and DC-SIGNR, which Are Novel Markers Expressed in Human Colon Cancer

Abstract: BackgroundColon cancer has always been diagnosed at a late stage, which is associated with poor prognosis. The currently used serum tumor markers CEA and CA19-9 display low sensitivity and specificity and may not have diagnostic value in early stage colon cancer. Thus, there is an urgent need to identify novel serum biomarkers for use in the early detection of colon cancer.MethodsIn this study, the expression of DC-SIGN and DC-SIGNR in serum was detected by enzyme-linked immunosorbent assay (ELISA). DC-SIGN an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 44 publications
(53 reference statements)
0
40
0
Order By: Relevance
“…[125][126][127][128] Hes1, a downstream effector of Notch signaling, is important for stem cell maintenance, prevents quiescent cells from differentiation and apoptosis, and is implicated in cancer progression. 59,121,[129][130][131][132][133] Consistently, components of the FXR1a-microRNP are implicated in cancer progression: FXR1 is known to promote tumor invasion and progression, 30 while its interacting partners, PARN and p97, are increased in activity or levels in many cancers.…”
Section: Fxr1a-micrornp Mediates Translation Of Important Genesmentioning
confidence: 99%
“…[125][126][127][128] Hes1, a downstream effector of Notch signaling, is important for stem cell maintenance, prevents quiescent cells from differentiation and apoptosis, and is implicated in cancer progression. 59,121,[129][130][131][132][133] Consistently, components of the FXR1a-microRNP are implicated in cancer progression: FXR1 is known to promote tumor invasion and progression, 30 while its interacting partners, PARN and p97, are increased in activity or levels in many cancers.…”
Section: Fxr1a-micrornp Mediates Translation Of Important Genesmentioning
confidence: 99%
“…2). DC-SIGN is predominantly expressed on DCs, whereas DC-SIGNR and LSECtin are co-expressed by liver and lymph node sinusoidal endothelial cells (9,87). DC-SIGN, DC-SIGNR and LSECtin share common functions in that they serve as adhesion molecules and are involved in antipathogenic microorganism immunity (87).…”
Section: Dc-sign Family In Tumor Metastasismentioning
confidence: 99%
“…The association between DC-SIGN and LSECtin and tumor metastasis has been further demonstrated. Jiang et al (9) reported high expression levels of DC-SIGN in colon cancer tissues, which correlated positively with stage III–IV disease (9). Thus, DC-SIGN is associated with the metastatic potential of colon cancer cells, as lymphatic metastasis or distant organ metastasis are frequently present are in stages III–IV of disease.…”
Section: Dc-sign Family In Tumor Metastasismentioning
confidence: 99%
See 1 more Smart Citation
“…The side effects arise because of non-selective and specific target of the treatments. Therefore, more studies set to discover specific and selective colon cancer treatment [8,9,10] to kill colon cancer cells without endangering normal cells.…”
Section: Introductionmentioning
confidence: 99%